POVERTY AND SOCIAL EXCLUSION IN RURAL SERBIA – position of family farms - Bogdanov, Natalija; Cvejic, Slobodan (Economics of Agriculture, 2011)
This paper considers the social inclusion of rural areas in Serbia, with particular attention to financial poverty of farm households. Our focus is on the size and the causes of poverty. The research was conducted through a questionnaire survey on a stratified sample of rural households. The strata were defined as to reflect the heterogeneous geographical and socio-economic characteristics of the rural areas of Serbia. Financial poverty was measured in accordance with the EU methodology, i.e. on the basis of income rather than consumption - poverty line was defined as 60% median of total cash income of households by equivalent consumption unit on the national level. The results are presented according to type of households and rural regions.